2004
DOI: 10.1016/j.msea.2003.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-glide stresses on plastic flow: from atomistic to continuum modeling

Abstract: The Schmid law, which is accurate for face-centered-cubic (fcc) metals, assumes that only the shear stress acting in the slip plane in the slip direction controls the plastic deformation. Hence, it is implicitly assumed that the critical resolved shear stress (CRSS) for the slip is not affected by any other components of the applied stress tensor. This rule is almost ubiquitously utilized in large-scale continuum computations of plastically deforming single and polycrystals. On the other hand, in materials wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 54 publications
2
62
0
1
Order By: Relevance
“…For equal yield stresses in tension and compression c=0, hence the proposed criterion reduces to the von Mises yield criterion. It was shown that this isotropic yield criterion describes with great accuracy the crystal plasticity simulation results of Hosford and Allen [140] and of Vitek et al [286] for randomly oriented polycrystals (for more details, see Cazacu and Barlat [75]). The isotropic criterion (13) was further extended such as to incorporate anisotropy using the generalized invariants approach i.e.…”
Section: Classical Anisotropic Yield Functionsmentioning
confidence: 81%
“…For equal yield stresses in tension and compression c=0, hence the proposed criterion reduces to the von Mises yield criterion. It was shown that this isotropic yield criterion describes with great accuracy the crystal plasticity simulation results of Hosford and Allen [140] and of Vitek et al [286] for randomly oriented polycrystals (for more details, see Cazacu and Barlat [75]). The isotropic criterion (13) was further extended such as to incorporate anisotropy using the generalized invariants approach i.e.…”
Section: Classical Anisotropic Yield Functionsmentioning
confidence: 81%
“…This means that the CPFE method has evolved as an attempt to employ some of the extensive knowledge gained from experimental and theoretical studies of single-crystal deformation and dislocations to inform the further development of continuum field theories of deformation. The general framework supplied by variational crystal plasticity formulations provides an attractive vehicle for developing a comprehensive theory of plasticity that incorporates existing knowledge of the physics of deformation processes [8][9][10] into the computational tools of continuum mechanics [11,12] with the aim of developing advanced and physically based design methods for engineering applications [13].…”
Section: Crystalline Anisotropy and The Spirit Of The Crystal Plasticmentioning
confidence: 99%
“…Alternative flow criteria to the classical Schmid law form which are investigated in different contexts, see for example (Vitek et al, 2004) but also (Franciosi and Zaoui, 1991;Franciosi and Berbenni, 2008), can also require, in general, reconsideration of the underlying hardening mechanisms. In the particular case of BCC crystals, it has been discussed in details in ) that when the critical stress to attain slip activity is no more a pure shear on a slip plane but a stress combination, the hardening model becomes more complex than the simple (and widely efficient) forest model and is still to be explicated.…”
Section: Analyses Of the Stress-strain Curvesmentioning
confidence: 99%